Light quark physics on different lattices - Chris Allton (1993)
The light quark results from three different simulations are summarized. We get consistent results, within our statistics, between smeared and non smeared data. A comparison is performed with similar results from the UKQCD collaboration. All runs have been performed on two 6.4 GF APE computers \cite{tubo}.